The Influence of Solvent and Heating Time Toward the Percent Yield of Sumbermanjing Pyrophyllite-Polyethylene Glycol (PEG) 6000 Composites - Siti Mutrofin; Ekantoro Ekantoro; Rurini Retnowati; Hanisah Kamilah (UNIVERSITAS SEBELAS MARET (UNS), 2026)
The synthesis of clay-polymer composites has attracted considerable interest due to their promising potential properties. The composites were prepared from Sumbermanjing pyrophyllite and polyethylene glycol (PEG) 6000. This research aims to evaluate the influence of solvent and heating time on the percent yield of the composites. Pyrophyllite-PEG composites were synthesized via the casting and sol-gel methods with variations in solvent (demineralized water, methanol, acetone) and heating time (1, 1.5, and 2 hours). The highest yield (37.7239%) was achieved by a composite synthesized with acetone and a 2-hour heating treatment. The composite prepared with demineralized water showed poorer PEG diffusion into the pyrophyllite structure than did those prepared with methanol or acetone. A 2-hour treatment produced a more uniform, relatively smaller porous structure, despite subtle differences across various heating conditions. Statistical analysis revealed a significant difference among solvent treatments, but no significant difference among heating times. The melting points of the 1-hour and 2-hour composites were 120.7667 °C and 116.0333 °C, respectively, suggesting a successful composite synthesis. The successful composite synthesis was further confirmed by Fourier Transform Infrared (FTIR) spectra, which showed characteristic functional groups (O–H stretching, 3673.92 cm-1; C–H stretching, 2882.37 cm-1; Al–OH stretching, 1146.67 cm-1).